2002
DOI: 10.1259/bjr.75.899.750884
|View full text |Cite
|
Sign up to set email alerts
|

Colour Doppler and grey scale ultrasound features of HIV-related vascular aneurysms

Abstract: Atypical aneurysms of large elastic arteries owing to human immunodeficiency virus (HIV) vasculopathy are a well described complication of acquired immunodeficiency syndrome (AIDS). However, there are no reports describing the ultrasound features of these lesions. We performed a retrospective review of ultrasound images of 12 patients presenting with 39 HIV-related aneurysms over a 2 year period. Of these there were a total of 12 patients with symptomatic lesions comprising the superficial femoral artery (n=5)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…As a general principle, aneurysms found clinically at one location guided the screening for aneurysms at other locations. Duplex ultrasound features characterised by forward and backward flow within a pseudo-aneurysm are reflected as a ‘yin-yang’ sign 32 (Fig. 2D) , cavitational echogenicity and turbulent flow with a vessel wall defect (Fig.…”
Section: Imaging Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As a general principle, aneurysms found clinically at one location guided the screening for aneurysms at other locations. Duplex ultrasound features characterised by forward and backward flow within a pseudo-aneurysm are reflected as a ‘yin-yang’ sign 32 (Fig. 2D) , cavitational echogenicity and turbulent flow with a vessel wall defect (Fig.…”
Section: Imaging Studiesmentioning
confidence: 99%
“…2E) . 32 This pathological process is eclipsed by adjacent hypo-echoic spotting and vessel wall thickening with normal proximal and distal vasculature. Patients deemed suitable for surgery are subjected to definitive imaging in the form of angiography or computerised tomographic angiography.…”
Section: Imaging Studiesmentioning
confidence: 99%
“…4). Yin-yang sign was originally used to describe the swirling pattern seen on color-flow Doppler sonography secondary to intermittent blood flow into and out of a pseudoaneurysm lumen [9]. Subsequently, it was described in contrast CT of a partially thrombosed aneurysm with the areas of hyper-attenuation indicating partially contrast-filled lumen and the areas of hypo-attenuation indicating the presence of mural thrombus [1,10].…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that endothelial cell dysfunction may play a role, as a predisposing factor for primary thrombosis. Hypercoagulable states associated with the HIV infection, including antiphospholipid antibody syndrome, deiciencies in free protein S, protein C, and antithrombin III, could predispose patients to arterial thrombosis [18,19].…”
Section: Hiv-associated Vascular Thrombosismentioning
confidence: 99%